Special issue: practice and intervention research. (Social Work Research, 2001)
A special issue on practice and intervention research in social work. Topics discussed include research on social work interventions; a 12-month follow-up study on the effect of HIV/AIDS prevention intervention for Israeli adolescents in residential centers; the evaluation of a sexual assault and dating violence prevention program for urban youths; client participation and outcomes of intensive family preservation services; and the analysis of single subject design data using statistical process control charts.